Evidence for the Reliability and Validity of the Internalized AIDS-Related Stigma Scale in Rural Uganda - Tsai, Alexander C.; Weiser, Sheri D.; Steward, Wayne T.; Mukiibi, Nozmo F. B.; Kawuma, Annet; Kembabazi, Annet; Muzoora, Conrad; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R. (AIDS and Behavior, 2013)
HIV infection remains highly stigmatized throughout sub-Saharan Africa despite the increasing availability of treatment. HIV-related stigma is commonly described to be highly prevalent in East Africa, but none of these studies have employed validated scales for measurement. We used data from 456 people living with HIV/ AIDS in rural Uganda to validate the six-item Internalized AIDS-Related Stigma Scale. The scale demonstrated acceptable internal consistency (Cronbach’s alpha = 0.73) and time stability. Exploratory factor analysis indicated the presence of a single factor. Construct validity was supported by observations that the scale was correlated with related constructs such as depression and mental health related quality of life. The scale was able to discriminate between groups of persons who were different in terms of treatment status and their experience of HIV-related self-blame. Taken together, these findings suggest that the Internalized AIDS-Related Stigma Scale may be a useful tool for socio-behavioral HIV research.
Keywords: HIV; Social stigma; Uganda